Compassionate goals, innovation and well-being in Brazilian and Portuguese organizations: The mediating role of social safeness - Junça Silva, A.; Mendonça, H.; Ferreira, M. C.; Caetano, António (9th European IACCP Conference, 2017)
Building on attachment theory and the tripartite model of affect regulation, this study aims to test a model about the relationships of compassionate goals with innovative work behavior and wellbeing at work. The mediating role of social safeness in these relationships is also tested. Specifically, it was hypothesized that employees with more compassionate goals would experience a higher social safeness and, in turn, more innovative work behavior and wellbeing at work. A survey was conducted on two sample of employees from, respectively, Brazilian public and private organizations (N = 127), and Portuguese private organizations (N = 232). Data were collected at two points in time and structural equation modeling was used to analyze them. Compassionate goals (Time 1) were found to be indirectly related to innovative work behavior (Time 2) and to wellbeing at work (Time 2) through increased social safeness (Time 2).